Study of the Effects of ATP Suppliers and Thiol Reductants on Toxicity of Pioglitazone in Isolated Rat Liver Mitochondria - Rezaiean Mehrabadi, Abbas (Iran J Pharm Res, 2015)
Pioglitazone (PG) is one of thiazolidinediones used for the treatment of type II diabetes mellitus. Some reports of its hepatotoxicity exist, but the mechanism of its hepatotoxicity is not well known. In the present study, the protective effect of some ATP suppliers are investigated against mitochondrial toxicity of PG in isolated rat mitochondria. Mitochondrial viability was investigated by MTT assay. The effects of PG on superoxide dismutase activity, ATP production, mitochondrial swelling and oxidative stress were also investigated. PG reduced mitochondrial viability with an LC(50) of 880±32 µM. It reduced ATP production and superoxide dismutase activity in mitochondria and increased mitochondrial swelling, but no oxidant effect was present as measured by TBARS formation. Fructose, dihydroxyacetone, dithioteritol, and N-acetylcysteine reduced mitochondrial toxicity of PG. Therefore, PG toxicity may be due to its mitochondrial toxicity and energy depletion, and ATP suppliers could be effective in preventing its toxicity.